Development of an IoE Framework and Dashboard for a Low Energy House Using Python - Thomas Omalla, Morgan Kadowa; mad kaidi, hazilah; Galabuzi, Chanda; Muhtazaruddin, Mohd Nabil; Sarip, Shamsul (International Journal of Integrated Engineering, 2025)
The field of Internet of Everything (IoE) represents a significant evolution in technology, building upon the foundation of the Internet of Things (IoT) by integrating not just devices, but people and processes as well. This paper addresses the challenge of enhancing a Smart Home environment by transitioning from a mere IoT setup to a comprehensive IoE framework. The research aimed to extend an existing IoT system to IoE by integrating additional components such as actuators, enhanced data analytics, and remote access, thereby connecting the unconnected in smart home setups. Key findings include a framework that recommends potential integration of sensors and actuators for automated home management, and the creation of a user-friendly dashboard for real-time monitoring and control. The study contributes to the field by demonstrating how an IoT system can be extended to IoE and in so doing improve energy efficiency and user experience in Smart Homes. It also highlights potential security and privacy challenges inherent in such interconnected systems.